PEMBUATAN SISTEM PENGUKURAN VISKOSITAS FLUIDA SECARA DIGITAL MENGGUNAKAN SENSOR EFEK HALL UGN3503 BERBASIS ARDUINO UNO328 - Tissos, Nurry Putri; Yulkifli, Yulkifli; Kamus, Zulhendri (Sainstek : Jurnal Sains dan Teknologi, 2014)
he purpose of this research is to determine the performance specifications and design specifications of viscometer. Kind of this research is laboratory experiment. The result is the design of the measurement system consists of an UGN3503 sensor as the sensing iron ball and an electronic box, the system have the average relative accuracy is 96% with an average of 0.9706. The viscosity values for oil is 10,237 Pa s  and cooking oil of 2,286 Pa s.Key words : viscocity, arduino uno328, hall effect UGN3503